Challenges and innovations in chiral drugs in an environmental and bioanalysis perspective - Barreiro, Juliana Cristina [UNESP]; Tiritan, Maria Elizabeth; Cass, Quezia Bezerra (Elsevier, 2021)
The boundary of the chiral environmental, forensic and bioanalysis has been critically presented in this review. Important advances regarding chiral screening technology and their impact on method development and applications have been pointed out. The complexity of merging high efficiency enantioselectivity separation with the selected sample matrix and the intended goal of the analysis is not a trivial task and in many cases the application of the method is the main novelty. Regardless of the complexity of new applications on chiral separation analysis, the trend is towards reaching higher levels of detectability and lower sample volumes. An assorted variety of methods applications in environmental and bioanalysis, including demand in forensic analysis is herein concisely discussed.
Keywords: Biotransformation; Chiral 2D LC; Enantioseparation; Forensic chiral analysis; Metabolic profiling; Multi-residue; Supercritical fluid chromatography